Regulation of host and viral promoters during human cytomegalovirus latency via US28 and CTCF. (27th May 2021) - Elder, Elizabeth G.; Krishna, Benjamin A.; Poole, Emma; Perera, Marianne; Sinclair, John
Abstract : Viral latency is an active process during which the host cell environment is optimized for latent carriage and reactivation. This requires control of both viral and host gene promoters and enhancers often at the level of chromatin, and several viruses co-opt the chromatin organiser CTCF to control gene expression during latency. While CTCF has a role in the latencies of alpha- and gamma-herpesviruses, it was not known whether CTCF played a role in the latency of the beta-herpesvirus human cytomegalovirus (HCMV). Here, we show that HCMV latency is associated with increased CTCF expression and CTCF binding to the viral major lytic promoter, the major immediate early promoter (MIEP). This increase in CTCF binding is dependent on the virally encoded G protein coupled receptor, US28, and contributes to suppression of MIEP-driven transcription, a hallmark of latency. Furthermore, we show that latency-associated upregulation of CTCF represses expression of the neutrophil chemoattractants S100A8 and S100A9 which we have previously shown are downregulated during HCMV latency. As with downregulation of the MIEP, CTCF binding to the enhancer region of S100A8/A9 drives their suppression, again in a US28-dependent manner. Taken together, we identify CTCF upregulation as an important mechanism for optimizing latent carriage of HCMV at both the levels of viral and cellular gene expression.